1996
DOI: 10.1155/1997/49681
|View full text |Cite
|
Sign up to set email alerts
|

Nonabsorbable Antibiotics Reduce Bacterial and Endotoxin Translocation in Hepatectomised Rats

Abstract: There is increasing evidence that septic complications, occurring after major hepatectomies, may be caused by gram negative bacteria, translocating from the gut. We investigated in rats, the effect of extended hepatectomy on the structure and morphology of the intestinal mucosa as well as on the translocation of intestinal bacteria and endotoxins. We also examined the effect of nonabsorbable antibiotics on reducing the intestinal flora and consequently the phenomenon of translocation by administering neomycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
7
0
3
Order By: Relevance
“…Our results confirm previous reports on bacterial and endotoxin translocation after hepatectomy, demonstrating significantly increased endotoxin concentrations in portal and aortic blood [1,26]. This study shows for the first time that administration of BBS or NT effectively reduces endotoxemia in hepatectomized rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results confirm previous reports on bacterial and endotoxin translocation after hepatectomy, demonstrating significantly increased endotoxin concentrations in portal and aortic blood [1,26]. This study shows for the first time that administration of BBS or NT effectively reduces endotoxemia in hepatectomized rats.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it seems that liver regeneration is a process that takes place under low oxidative stress conditions. Partial hepatectomy-induced alterations on intestinal oxidative state have not been adequately elucidated, and most studies up to now have focused on morphological or submicroscopic alterations of the intestinal mucosa and intestinal flora disturbances [1,26]. According to our results, partial hepatectomy decreases lipid peroxidation and glutathione oxidation in the intestine, while increases protein oxidation, indicating that these processes are modulated by different mechanisms in this organ.…”
Section: Discussionmentioning
confidence: 62%
“…Kakkos et al 26 reported that administration of nonabsorbable antibiotics had a positive effect on bacterial and endotoxin translocation after extended hepatectomy, and related this to reduction of colonic bacterial load as an intraluminal effect of antibiotics. Our study has demonstrated that ampicillin-sulbaktam administration reduces the level of bacterial translocation.…”
Section: Table 2 the Average Of Serum Bilirubin Alt Ast And Alp Valmentioning
confidence: 99%
“…The cecal contents of the gut were collected by the following technique [9]. The ascending colon was ligated and a needle was introduced in to the cecum through the ileocecal valve with 2 mL of sterile saline infused in the cecum, the needle was withdrawn and the terminal ileum was ligated.…”
Section: Bacterial Studiesmentioning
confidence: 99%